2021
DOI: 10.1021/acsnano.1c03698
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Intercalation Growth of Scalable Hexagonal Boron Nitride/Graphene Bilayer Moiré Materials with Highly Convergent Interlayer Angles

Abstract: Vertically stacked two-dimensional van der Waals (vdW) heterostructures with specific interlayer angles exhibit peculiar physical properties. Nowadays, most of the stacked layers are fabricated by mechanical exfoliation followed by precise transfer and alignment with micrometer spatial accuracy. This stringent ingredient of sample preparation limits the productivity of device fabrication and the reproducibility of device performance. Here, we demonstrate the one-pot chemical vapor deposition growth of hexagona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Since hydrogen stabilizes the edges of hBN grains rather than the Cu surface, the energy is low enough for the B and N adatoms to locate between the Cu surface and hBN layers. Hence, they can diffuse underneath the as-grown hBN layer to form the multilayer hBN . So far, the growth mechanism of multilayer hBN still needs to be further explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since hydrogen stabilizes the edges of hBN grains rather than the Cu surface, the energy is low enough for the B and N adatoms to locate between the Cu surface and hBN layers. Hence, they can diffuse underneath the as-grown hBN layer to form the multilayer hBN . So far, the growth mechanism of multilayer hBN still needs to be further explored.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, they can diffuse underneath the as-grown hBN layer to form the multilayer hBN. 32 So far, the growth mechanism of multilayer hBN still needs to be further explored.…”
Section: Energetic Preference Of Cvd Hbnmentioning
confidence: 99%
“…However, the progress in this direction is not promising as most of the structures obtained either have the R-type (0°) stacking orientations or the H-type (60°) stacking orientations, as they are energetically favorable in the CVD growth process ( Liu et al., 2014 ). Few strategies, including heterosite nucleation ( Sun et al., 2021 ), temperature triggered misalignment ( Omambac et al., 2019 ), metal-semiconductor stacking ( Li et al., 2020a ), epitaxial intercalation of graphene under hydrogen-terminated hBN template ( Wang et al., 2021a ), are recently reported that showed the potential of CVD to generate moiré phase. Still, stringent control on interlayer twist angle is challenging and needs to be encountered soon.…”
Section: Excitons In Tmds Based Heterostructuresmentioning
confidence: 99%
“…It is worth noting that intercalation has also been observed during epitaxial growth of h-BN/graphene heterostructures on metals. [9,10] If, on the one hand, intercalation during vdW epitaxy is unwanted, it also represents a very promising path for the controlled synthesis of novel material systems. In fact, Al Balushi et al [11] developed an experimental scheme that enhanced the intercalation of Ga and N species below epitaxial graphene on SiC(0001), which allowed for the realization of a 2D-like GaN phase encapsulated between graphene and SiC(0001).…”
Section: Introductionmentioning
confidence: 99%